Digital modernization of sectoral market regulation mechanisms in the context of post-war reconstruction: novel digital solutions for Ukraine’s brewing industry - Soroka, Bohdan; Soroka, Artem (Pressing Problems of Public Administration, 2025)
This article examines the challenge of digital modernisation of public administration mechanisms for sectoral markets in the context of Ukraine’s post-war reconstruction, with a focus on the brewing industry as a model sector for implementing innovative regulatory approaches. The authors analyse global challenges facing traditional centralised control systems, which demonstrate critical efficiency limitations amid transforming consumer preferences and growing competition from alternative beverages. The methodological foundation of the research is adaptive public administration theory combined with concepts of digital governance and the «government-as-a-platform» approach. The study employs dynamic comparative analysis of regulatory strategies in the USA, Australia, Singapore, and Estonia, revealing a digitalisation paradox: even in technologically progressive countries, specialised support programmes for craft breweries through blockchain instruments are virtually non-existent, whilst small producers continue to rely on traditional financing with high interest rates.The key scientific contribution is the development of a hybrid public administration model based on contractual relationship tokenisation, integrating blockchain platforms with traditional banking escrow accounts. Unlike classical approaches of state intervention through subsidies, the model is based on the «government-as-catalyst» concept, where public institutions create legal and institutional frameworks for market innovations without direct financing of technological solutions. The practical significance of the research lies in developing specific mechanisms for automating the execution of commercial contracts between craft breweries, distributors, and raw material suppliers whilst simultaneously ensuring transparency for tax authorities. The proposed solutions are demonstrated through three realistic examples of tokenised operations, showing possibilities for reducing working capital financing costs by 30-50%, decreasing non-payment risks to 5-8%, and automating tax reporting in real-time. The results have potential for adaptation in other food industry and agricultural sectors, creating a multiplicative effect for regional economic development. The model contributes to developing digital competencies in public administration and enhancing small business competitiveness in the context of Ukraine’s European integration.